A Geospatial Analysis of Health, Mental Health, and Stressful Community Contexts in Los Angeles County - Robles, Brenda (Prev Chronic Dis, 2019)
INTRODUCTION: Despite numerous federal investments, chronic disease continues to disproportionately affect certain communities across the United States. Understanding the regional distribution (including any overlaps) of factors that extend beyond built and food environments, especially factors that may adversely affect chronic disease–related behaviors, is important. This case study of Los Angeles County’s geospatial landscape sought to address these gaps in research and practice. METHODS: We examined the distributions and geographic overlaps between economic hardship, psychological distress, soda consumption, and availability of publicly funded mental health facilities in 8 Service Planning Areas in Los Angeles County. We categorized the geospatial presence of each variable as low, intermediate, or high. We imported all data, collected during 2014–2018, into ArcGIS Pro version 2.3.3 to create 5 bivariate choropleth maps. RESULTS: Levels of economic hardship were not equally distributed across communities; the county was characterized by intermediate levels of soda consumption and psychological distress. Most areas had low or intermediate availability of publicly funded mental health facilities. We also found some discordance between psychological distress and availability of publicly funded mental health facilities, and between economic hardship and availability of these facilities. CONCLUSION: The need exists to address disparities in economic hardship and to increase access to publicly funded mental health supports and providers in Los Angeles County. The information collected in this case study has policy implications for health, public health, and mental health services planning at the local level.